Intra-individual comparison of appetitive trace and delay conditioning in humans across acquisition and extinction - Finke, Johannes B.; Schippers, Anna M.; Klucken, Tim (Scientific reports, 2025)
Temporal contiguity between conditioned (CS) and unconditioned stimuli (US) is a crucial factor in Pavlovian learning, yet little is known about its role in appetitive conditioning and extinction. In a within-subject design, 60 participants underwent both a delay (DC) and trace conditioning (TC) session with partial reinforcement (75%) by monetary rewards (US) and varying interval between CS offset and US onset (DC: 0s; TC: 4s). In addition to self-report indices (reward expectancy, arousal, valence), psychophysiological markers (pupil dilation, heart-period and startle reflex modulation) were recorded during acquisition and extinction training. For most measures, significant differential conditioned responses emerged, irrespective of temporal contiguity, with no major differences observed between TC and DC during acquisition (except for potentially diminished startle attenuation in TC). Despite overall similar patterns in conditioned responding (with small to moderate effects on physiological measures), there was no intraindividual concordance between sessions, yet evidence for differential TC effects on extinction learning. Specifically, smaller reductions in differential reward expectancy, heart-period deceleration and startle modulation after extinction in TC suggested relatively diminished extinction learning. Conditioned pupil dilation (0–2 s after CS onset) remained comparatively stable. Taken together, our findings extend evidence of differences in underlying learning mechanisms between TC and DC to the context of reward learning.